1998
DOI: 10.1002/(sici)1098-2337(1998)24:6<421::aid-ab3>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Extremes of self-esteem and narcissism and the experience and expression of anger and aggression

Abstract: This study examined the level of self‐esteem and narcissism as personality variables involved in the disposition to experience and express anger. Three hundred thirty‐eight subjects were sampled across two higher education centres and one student teaching programme in the United Kingdom. It was reasoned that individuals with both high self‐esteem and narcissism would report especially high tendencies to experience and express anger and aggression and that those with high self‐esteem and low narcissism would re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(23 citation statements)
references
References 48 publications
1
17
0
3
Order By: Relevance
“…Papps and O"Carroll (1998) found that narcissists who are high in selfesteem experience anger and express aggression more than non-narcissistic and low-or high self-esteem individuals. The combination of impulsivity, the constant maintenance of their grandiose self-views, and intense experience of anger makes the narcissist especially prone to aggressive behavior in response to a perceived slight.…”
Section: Narcissismmentioning
confidence: 99%
See 1 more Smart Citation
“…Papps and O"Carroll (1998) found that narcissists who are high in selfesteem experience anger and express aggression more than non-narcissistic and low-or high self-esteem individuals. The combination of impulsivity, the constant maintenance of their grandiose self-views, and intense experience of anger makes the narcissist especially prone to aggressive behavior in response to a perceived slight.…”
Section: Narcissismmentioning
confidence: 99%
“…These results indicate that youth characterized by narcissistic traits are especially prone to behave impulsively and irresponsibly, to experience intense emotions (e.g., anger, worry), and to have trouble controlling their emotions. These findings are consistent with results for non-referred adult populations, such that individuals with narcissistic traits versus those without experience more intense anger, express more aggression (Papps & O"Carroll, 1998;Washburn et al, 2004), and are more behaviorally impulsive (Vazire & Funder, 2006). This combination of narcissistic traits with emotional and behavioral dysregulation may make youth especially unstable and volatile, committing acts of aggressive behavior as a result of intense anger and poor impulse control due to perceived slights to their self-image.…”
Section: Narcissistic Traitsmentioning
confidence: 99%
“…The focus of the present study, however, was not upon the clinical or abnormal psychological aspects of personality or the self and it should be noted that most of the research in the field of narcissism and its correlates has generally employed nonclinical samples (Papps & O'Carroll, 1998). To be more precise, certain narcissistic characteristics typically present as continua, as do many other psychological constructs including self-esteem (Hoyle, Kernis, Leary, & Baldwin,…”
Section: Introductionmentioning
confidence: 93%
“…Factors with potential to be psychologically meaning ful, but requiring further exploration, the 'worth looking at' category, include: adversarial sexual orientation (Malamuth 1991); fragile narcissism, which has been associated with aggression in response to threats to a grandiose selfimage (Bushman 1998;Papps 1998;Stuker 2002); and sexual entitlement (Hanson 1994.…”
Section: Risk Factors That Are 'Worth Looking At'mentioning
confidence: 99%